2020
DOI: 10.3390/app10082658
|View full text |Cite
|
Sign up to set email alerts
|

2-LED-µSpectrophotometer for Rapid On-Site Detection of Pathogens Using Noble-Metal Nanoparticle-Based Colorimetric Assays

Abstract: Novel point-of-care compatible methods such as colorimetric assays have become increasingly important in the field of early pathogen detection. A simple and hand-held prototype device for carrying out DNA-amplification assay based on plasmonic nanoparticles in the colorimetric detection is presented. The low-cost device with two channels (sample and reference) consists of two spectrally different light emitting diodes (LEDs) for detection of the plasmon shift. The color change of the gold-nanoparticle-DNA conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…reported in the literature. [263][264][265][266] Various scientific reports have also reported gold nanoparticle-based microfluidic devices as chemical-sensing agents (Cocaine, codeine, methamphetamine, cysteine, hemoglobin, etc., detection). [263,267,268] Notably, Ameku et al, reported a dual detection lab-on-chip device (Figure 17) by immobilizing GNPs for SERS and electrochemical sensing of cocaine for forensic application.…”
Section: Cytokine Flow and Severe Respiratory Syndromementioning
confidence: 99%
“…reported in the literature. [263][264][265][266] Various scientific reports have also reported gold nanoparticle-based microfluidic devices as chemical-sensing agents (Cocaine, codeine, methamphetamine, cysteine, hemoglobin, etc., detection). [263,267,268] Notably, Ameku et al, reported a dual detection lab-on-chip device (Figure 17) by immobilizing GNPs for SERS and electrochemical sensing of cocaine for forensic application.…”
Section: Cytokine Flow and Severe Respiratory Syndromementioning
confidence: 99%
“…5.3. Plasmonic Nanoparticles in DNA Amplification Assays C. Reuter et al [74] introduced a low-cost, simple prototype device (2-LED-µSpectrophotometer) for performing colorimetric DNA-amplification assay. The colorimetric sensing principle was based on salt or pH-induced aggregation of AuNPs, functionalized with oligonucleotides, which led to plasmon shift in the spectrum and solution color change.…”
Section: Paper-based Bioanalytical Systems Using Sensor Particlesmentioning
confidence: 99%